Application of organoid culture from HPV18‐positive small cell carcinoma of the uterine cervix for precision medicine. (23rd January 2023) - Kusakabe, Misako; Taguchi, Ayumi; Tanikawa, Michihiro; Hoshi, Daisuke; Tsuchimochi, Saki; Qian, Xi; Toyohara, Yusuke; Kawata, Akira; Wagatsuma, Ryota; Yamaguchi, Kohei; Yamamoto, Yoko; Ikemura, Masako; et al.
Abstract: Background: Small cell carcinoma of the uterine cervix (SCCC) is a rare and highly malignant human papillomavirus (HPV)‐associated cancer in which human genes related to the integration site can serve as a target for precision medicine. The aim of our study was to establish a workflow for precision medicine of HPV‐associated cancer using patient‐derived organoid. Methods: Organoid was established from the biopsy of a patient diagnosed with HPV18‐positive SCCC. Therapeutic targets were identified by whole exome sequencing (WES) and RNA‐seq analysis. Drug sensitivity testing was performed using organoids and organoid‐derived mouse xenograft model. Results: WES revealed that both the original tumor and organoid had 19 somatic variants in common, including the KRAS p.G12D pathogenic variant. Meanwhile, RNA‐seq revealed that HPV18 was integrated into chromosome 8 at 8q24.21 with increased expression of the proto‐oncogene MYC . Drug sensitivity testing revealed that a KRAS pathway inhibitor exerted strong anti‐cancer effects on the SCCC organoid compared to a MYC inhibitor, which were also confirmed in the xenograft model. Conclusion: In this study, we confirmed two strategies for identifying therapeutic targets of HPV‐derived SCCC, WES for identifying pathogenic variants and RNA sequencing for identifying HPV integration sites. Organoid culture is an effective tool for unveiling the oncogenic process of rare tumors and can be a breakthrough for the development of precision medicine for patients with HPV‐positive SCCC. Abstract : We confirmed two strategies for identifying therapeutic targets of human papillomavirus (HPV)‐derived small cell carcinoma of the uterine cervix (SCCC), whole exome sequencing for identifying pathogenic variants and RNA sequencing for identifying HPV integration sites. Organoid culture is an effective tool for unveiling the oncogenic process of rare tumors and can be a breakthrough for the development of precision medicine for patients with HPV‐positive SCCC.